2005
DOI: 10.1111/j.1469-7610.2004.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of task and subject variables among continuous performance tests

Abstract: Different combinations of target paradigm and target density appear to yield scores that are conceptually and psychometrically distinguishable. Consequently, developmentally appropriate interpretation of error rates across tasks may require (a) careful analysis of working memory and attentional resources required for successful performance, and (b) normative data bases that are differently stratified with respect to combinations of age and intelligence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Children's accuracy and reaction time show significant changes due to target density manipulations and the differential demands they place on working memory (Denney et al 2005;Losier et al 1996). A significant target density moderator effect would indicate that other factors, such as increased demand on the central executive system for switching between stimuli or between phonological and visual-spatial working memory subsystems (Baddeley 1996), influence BI effects.…”
Section: Stop-signal Target Densitymentioning
confidence: 96%
“…Children's accuracy and reaction time show significant changes due to target density manipulations and the differential demands they place on working memory (Denney et al 2005;Losier et al 1996). A significant target density moderator effect would indicate that other factors, such as increased demand on the central executive system for switching between stimuli or between phonological and visual-spatial working memory subsystems (Baddeley 1996), influence BI effects.…”
Section: Stop-signal Target Densitymentioning
confidence: 96%
“…A double-letter high target density version of the CPT was selected due to its association with high rates of both omission and commission errors (Denney et al 2005). The task displayed a total of 540 letters one at a time at a rate of 0.8 s per letter with an inter-trial interval of 0.2 s between each letter.…”
Section: Impulsivitymentioning
confidence: 99%
“…CPT variants (e.g., vigilance, n-back tasks) characteristically require children to respond to infrequently occurring, phonologically encoded stimuli (e.g., letters or numbers; Nichols and Waschbusch 2004), whereas visual match-to-sample (VMTS) tasks require rapid discrimination among visuospatial stimuli (Carlson et al 1986;Inoue et al 1998;Rapport et al 1996). Impulsive responding on these tasks may reflect distinct or combined underlying executive function (EF) deficits due to cognitive processing differences associated with how task stimuli are encoded (phonologically, visuospatially), and the degree of inhibitory control and working memory processes required by the tasks (Denney et al 2005;Klein et al 2006). To date, however, no study has investigated whether deficiencies in specific executive functions mediate ADHD-related commission errors on paradigm-specific tasks.…”
mentioning
confidence: 98%
“…Subject variables such as age and intelligence have been evaluated by some researchers for CPT tests (e.g., Denney, Rapport, & Chung, 2005). Personality and vigilance studies have mainly found that higher extraversion is associated with lower vigilance (Davies & Parasuraman, 1982: Koelega, 1992.…”
mentioning
confidence: 99%